Development of Pichia pastoris as a production system for HPV16 L1 virus-like particles as component to a subunit vaccine - Kotze, Lara (Stellenbosch : University of Stellenbosch, 2008)
Human papillomavirus (HPV) is a sexually transmitted virus and known precursor to cervical cancer, the second most lethal cancer in females across the world. Two virus-like particle (VLP) vaccines exist that provide immunity against the main serotypes of the disease and are produced in Saccharomyces cerevisiae (S. cerevisiae) and baculovirus infected insect cells. Pichia pastoris (P. pastoris) was chosen as an alternative expression system for HPV VLP production based on its history as prolific heterologous protein producer that circumvent many of the problems associated with aforementioned expression systems. The strongly inducible AOX promoter allows three-phase fermentations (1.3 L bioreactors) in which high cell densities (>100gCDW.L-1) are obtained prior to induction with methanol. During the induction phase the dissolved oxygen concentration may be used to control addition of methanol. It is also possible to use predetermined methanol feed rates and to adjust the amount of additional oxygen sparged to maintain a constant dissolved oxygen level. The effects of these control strategies, different gene constructs and multiple gene integrations were quantified through monomer-, VLP- and mRNA production levels. Increased biomass concentrations in the 20% dissolved oxygen control strategy led to the highest volumetric VLP concentration (68.53 mg.L-1). VLPs were located intracellularly in both the cytoplasm and membranes of the yeast cells. Despite lower codon adaptation of the h-L1 gene expressed in the X33[h-L1] strain it still had higher volumetric VLP concentrations under 40% dissolved oxygen control than the X33[Syn-L1] and X33[SA-L1] strain containing the SA-L1 and Syn-L1 genes. This was ascribed to the possible presence of rare codons in the Syn-hL1 and SA-L1 genes and a lower A+T content in the h-L1 gene. Multiple gene integrations of the h-L1 gene had a negative effect on VLP production and this conclusion was supported by lower mRNA concentrations indicating lower transcriptional efficiency. Increased methanol induction efficiency in the DO control strategies was indicated by higher specific L1 monomer levels. Decreased VLP to monomer ratios in the DO control strategies indicated that a bottleneck existed in the assembly process due to increased L1 monomer concentrations. Due to the hydrophobic region on the L1 protein, these proteins associated with the membranes within the yeast cells especially when efficient assembly to VLPs did not occur. HPV16 L1 VLP concentrations obtained in P. pastoris in this study are comparable to the study by Li et al., (2003), but much lower than expression levels obtained in baculovirus infected insect cells. Based on the expression levels of HBsAg VLPs obtained in P. pastoris, this system, with the necessary recommended optimisation, has the capacity for increased HPV VLP production ability.